From history to theory - Klein, Kerwin Lee, 1961- (University of California Press, 2011)
This work describes major changes in the conceptual language of the humanities, particularly in the discourse of history. In seven closely related essays, the author traces the development of academic vocabularies through the dynamically shifting cultural, political, and linguistic landscapes of the 20th century.